2005
DOI: 10.1351/pac200577020399
|View full text |Cite
|
Sign up to set email alerts
|

Deposition mechanism of nanostructured thin films from tetrafluoroethylene glow discharges

Abstract: Nanostructured polytetrafluoroethylene (PTFE)-like thin films can be deposited, in certain experimental conditions, by modulated discharges fed with tetrafluoroethylene (TFE). These coatings are characterized by a unique morphology consisting of highly twisted micron-long ribbons, which leads to an extremely high water repellency of the surface. In the present work, the diagnostics of the plasma phase is presented, coupled with that of the coating, in order to understand the film growth mechanism in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 43 publications
6
53
0
Order By: Relevance
“…3(i) and (ii)). In addition to the early works mentioned above, we note also the work of Favia [54], and Milella for modulated plasmas exploring the mechanisms to deposit ribbon-like or bumpy fluorocarbon layers [55], as reviewed also by the same author later on [56]. Vacuum deposition of superhydrophobic coatings was also reviewed by Cigala et al [57], and Kylian et al [18].…”
Section: Randomly Nanostructured Surfaces Via Plasma Etching or Deposmentioning
confidence: 79%
See 1 more Smart Citation
“…3(i) and (ii)). In addition to the early works mentioned above, we note also the work of Favia [54], and Milella for modulated plasmas exploring the mechanisms to deposit ribbon-like or bumpy fluorocarbon layers [55], as reviewed also by the same author later on [56]. Vacuum deposition of superhydrophobic coatings was also reviewed by Cigala et al [57], and Kylian et al [18].…”
Section: Randomly Nanostructured Surfaces Via Plasma Etching or Deposmentioning
confidence: 79%
“…3(ii)); however a long deposition time was necessary (over 1 h) [60]. Mechanisms of plasma deposited nanotexture formation and transition from bump to ribbon structures were discussed by Milella [55].…”
Section: Randomly Nanostructured Surfaces Via Plasma Etching or Deposmentioning
confidence: 99%
“…These ribbon-like structures are formed during the plasma polymerization and are also visible on non-deformed samples. [26,[72][73][74][75][76] The topographical changes at the metal surface, which increased the roughness, proved to influence the adhesion properties and the coating integrity, leading to coating failures. As observed in Figure 3f, a crack aligned with the slip band was observed in the 15 min coated sample, indicating a lack of cohesion.…”
Section: Resultsmentioning
confidence: 99%
“…The deposition parameters (pressure and flow (Figure 4) [24][25][26][27]. It was suggested that under the above conditions low ion bombardment, and a low concentration of CF 2 radicals incident at the surface triggered diffusion-mediated film growth.…”
Section: Fluorocarbon Plasma Polymersmentioning
confidence: 99%